The Genome of Shaw's Sea Snake (Hydrophis curtus) Reveals Secondary Adaptation to Its Marine Environment. (28th February 2020) - Peng, Changjun; Ren, Jin-Long; Deng, Cao; Jiang, Dechun; Wang, Jichao; Qu, Jiangyong; Chang, Jiang; Yan, Chaochao; Jiang, Ke; Murphy, Robert W; Wu, Dong-Dong; Li, Jia-Tang
Abstract: The transition of terrestrial snakes to marine life ∼10 Ma is ideal for exploring adaptive evolution. Sea snakes possess phenotype specializations including laterally compressed bodies, paddle-shaped tails, valvular nostrils, cutaneous respiration, elongated lungs, and salt glands, yet, knowledge on the genetic underpinnings of the transition remains limited. Herein, we report the first genome of Shaw's sea snake ( Hydrophis curtus ) and use it to investigate sea snake secondary marine adaptation. A hybrid assembly strategy obtains a high-quality genome. Gene family analyses date a pulsed coding-gene expansion to ∼20 Ma, and these genes associate strongly with adaptations to marine environments. Analyses of selection pressure and convergent evolution discover the rapid evolution of protein-coding genes, and some convergent features. Additionally, 108 conserved noncoding elements appear to have evolved quickly, and these may underpin the phenotypic changes. Transposon elements may contribute to adaptive specializations by inserting into genomic regions around functionally related coding genes. The integration of genomic and transcriptomic analyses indicates independent origins and different components in sea snake and terrestrial snake venom; the venom gland of the sea snake harbors the highest PLA2 (17.23%) expression in selected elapids and these genes may organize tandemly in the genome. These analyses provide insights into the genetic mechanisms that underlay the secondary adaptation to marine and venom production of this sea snake.